The Impact of Communication Skills Training on Nurses’ Competencies and Stress-Coping Strategies in Palliative Care: A Study in Shymkent and Astana, Kazakhstan - Issenova , Balday; Aimbetova , Gulshara; Nailya, Talkimbayeva; Adilya , Shakhiyeva; Zhanat, Kozhekenova; Gulshat , Begimbetova; Maiya, Zhakupova; Akmaral , Aitmanbetova; Gulmira, Altynbayeva; Valikhan, Akhmetov (Bangladesh Journal of Medical Science, 2025)
Background Effective communication is a critical skill for nurses, particularly in palliative care, where emotional and complex patient interactions are common. Training nurses in communication skills may improve both their competence in patient interactions and their ability to manage the emotional demands of end-of-life care. Objective This study aimed to assess the impact of a training program on communication competencies and stress-coping strategies among nurses in two distinct regions, Shymkent and Astana, with a focus on palliative care settings. Methods A descriptive-analytical, cross-sectional study was conducted from January to December 2024 in two palliative care hospitals in Shymkent and Astana, Kazakhstan. Thirty nurses (15 from each hospital) participated. They completed a self-assessment of their communication skills before and after attending a communication skills training seminar, with follow-up assessments after six months. Two instruments were used: the Communicative Competence Scale (CCS) to measure communication skills and the Ways of Coping Questionnaire (WCQ) to assess coping strategies related to stress. Results Before training, nurses in Shymkent demonstrated significantly higher communication competence scores (M = 109.27) compared to those in Astana (M = 98.6). After training, both groups showed improvements in communication skills, with Astana nurses experiencing the most significant increase in their self-assessment scores (M = 106.13). Notably, nurses in Astana showed a marked improvement in coping strategies, including increased seeking of social support and decreased reliance on confrontational and distancing behaviors. Conclusion Communication skills training significantly enhances nurses’ communication competencies and coping strategies, particularly in regions where initial competencies were lower. These improvements may lead to better patient care and increased nurse well-being in palliative care settings. Further integration of communication training in nursing education is recommended. BJMS, Vol. 24 No. 03 July’25 Page : 957-966